The System of Industrial Relations in Canada - McPhillips, David C. (Relations industrielles / Industrial Relations, 1994)
The article reviews the book, "The system of industrial relations in Canada," 4th edition, by Alton W.J. Craig and Norman A. Solomon.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z